2016
DOI: 10.1007/s00432-016-2222-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a and miR-138 block the G1/S transition by targeting the cell cycle regulating network in prostate cancer cells

Abstract: The present findings suggest an anti-proliferative role for miR-26a and miR-138 in PCa by blocking the G1/S-phase transition independent of EZH2 but via a concerted inhibition of crucial cell cycle regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Interestingly, the present study showed that UC-MSCs decreased the mRNA level of CDK6 in both tumor cell lines, and also confirmed the expression at the protein level by reduction of CDK6 protein level in HL-60 cells. Furthermore, other studies also revealed that miR-34a, miR-26a, and miR-138 significantly diminished the expression of CCNE2 and CDK6 in tumor cells and arrested the cells at the G 1 /S transition 30,31 .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the present study showed that UC-MSCs decreased the mRNA level of CDK6 in both tumor cell lines, and also confirmed the expression at the protein level by reduction of CDK6 protein level in HL-60 cells. Furthermore, other studies also revealed that miR-34a, miR-26a, and miR-138 significantly diminished the expression of CCNE2 and CDK6 in tumor cells and arrested the cells at the G 1 /S transition 30,31 .…”
Section: Discussionmentioning
confidence: 87%
“…In concert with these ndings, our study demonstrates that lncRNA UPK1A-AS1 interacts with miR-138-5p that is reported to be a tumor suppressor in HCC. Of note, miR-138-5p was downregulated in HCC and acted as a tumor suppressor to inhibit several cell cycle-related genes like CDK6 [27][28][29]. Indeed, UPK1A-AS1-induced CDK6 overexpression is partially dependent on the activity of miR-138-5p, as overexpression of miR-138-5p can ablate UPK1A-AS1 activity in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miR-138-5p was downregulated in HCC and acted as a tumor suppressor to inhibit several cell cycle-related genes such as CDK6 [27][28][29]. Indeed, UPK1A-AS1-induced CDK6 overexpression was partially dependent on the activity of miR-138-5p, as overexpression of miR-138-5p ablated UPK1A-AS1 activity in HCC.…”
Section: Discussionmentioning
confidence: 99%